The Implementation of Knowledge Management System as the Basis for Public Services and Public Information in the Village Service Unit - Rizky Yananda; Husni Satra Mihardja; Gerry Firmansyah; Habibullah Akbar (Pelopor Publikasi Akademika, 2023)
The current technological development is progressing rapidly. However, the implementation of this technological advancement is still not optimally applied in all areas, especially in rural areas. Therefore, the application of Knowledge Management System (KMS) is necessary. According to Law Number 6 of 2014 concerning villages, in section 3 of the Village Law, Article 86 on the village information system and rural area development, it is stated in the first point that villages have the right to access information through the village information system developed by the local government of the district/city. Currently, the problems that occur in villages are the lack of maximum service and information, the scarcity of village officials in managing computerized data, and the lack of systematic archiving. By implementing KMS, it can be a solution for public services and information, as well as data processing and correspondence in the village, so that the community will receive excellent services from the village government.